The Relationship between Chemical Flexibility and Nanoscale Charge Collection in Hybrid Halide Perovskites. (15th March 2018) - Luo, Yanqi; Aharon, Sigalit; Stuckelberger, Michael; Magaña, Ernesto; Lai, Barry; Bertoni, Mariana I.; Etgar, Lioz; Fenning, David P.
Abstract: Hybrid organometal halide perovskites are known for their excellent optoelectronic functionality as well as their wide‐ranging chemical flexibility. The composition of hybrid perovskite devices has trended toward increasing complexity as fine‐tuned properties are pursued, including multielement mixing on the constituents A and B and halide sites. However, this tunability presents potential challenges for charge extraction in functional devices. Poor consistency and repeatability between devices may arise due to variations in composition and microstructure. Within a single device, spatial heterogeneity in composition and phase segregation may limit the device from achieving its performance potential. This review details how the nanoscale elemental distribution and charge collection in hybrid perovskite materials evolve as chemical complexity increases, highlighting recent results using nondestructive operando synchrotron‐based X‐ray nanoprobe techniques. The results reveal a strong link between local chemistry and charge collection that must be controlled to develop robust, high‐performance hybrid perovskite materials for optoelectronic devices. Abstract : Hybrid halide perovskite thin films exhibit complex chemistry at the nanoscale that can affect their optoelectronic performance. In situ characterization of chemistry and functionality, such as by operando X‐ray fluorescence and X‐ray beam induced current measurements of perovskite solar cells, reveals insights into the relationship between local current collection, nonstoichiometry, and chemistry composition in hybrid lead perovskite absorbers.